Synthesis and cytotoxic activities of novel copper and silver complexes of 1,3-diaryltriazene-substituted sulfonamides - Dilek Canakci; Ismail Koyuncu; Nabih Lolak; Mustafa Durgun; Suleyman Akocak; Claudiu T. Supuran (Taylor & Francis Group, 2019)
In this study, a series of 10 novel copper (II) and silver complexes of 1,3-diaryltriazene-substituted sulfonamides was synthesised. All the synthesised ligands and their metal complexes were assessed for in vitro cytotoxicity against human colorectal adenocarcinoma (DLD-1), cervix carcinoma (HeLa), breast adenocarcinoma (MDA-MB-231), colon adenocarcinoma (HT-29), endometrial adenocarcinoma (ECC-1), prostate cancer (DU-145 and PC-3), normal embryonic kidney (HEK-293), normal prostate epithelium (PNT-1A), and normal retinal pigment epithelium (ARPE-19) cells. Most of the metal complexes from the series showed to be more active against all cancerous cells than the uncomplexed 1,3-diaryltriazene-substituted sulfonamides, and lower cytotoxic effects observed on normal cells. Most of the Cu (II) and Ag (I) metal complexes from the presented series showed high cytotoxic activity against HeLa cells with IC50 values ranging from 2.08 to >300 µM. Specifically, compound L3-Ag showed one of the highest cytotoxicity against all cancer cell lines with IC50 values between 3.30 to 16.18 µM among other tested compounds.